Acute kidney injury in adults aged 60 years or older hospitalized with COVID-19 and association with mortality - Ingrid Ardisson Colodete; Caroline Delboni Nascimento; Sarah de Jesus Francisco; Manoela Morgado Horta Barros; Júlia Magalhães Monteiro; Júlia Andrade Rodrigues Alves; Caroline Maffei Spinassé; Caroline Tessinari Pupim; Julia Almenara Ribeiro Vieira; Renato Lirio Morelato (Brazilian Society of Geriatrics and Gerontology, 2024)
Objective: To analyze the presence of acute kidney injury (AKI) in hospitalized older patients with COVID-19 and its association with hospital mortality. Methods: This was a retrospective observational case-control study of patients over 60 years of age hospitalized from April 01, 2020, to April 30, 2021, at a ward or intensive care unit (ICU) dedicated to COVID-19. The severity of AKI was stratified according to the Kidney Disease: Improving Global Outcomes (KDIGO) criteria. Binary logistic regression was used to determine the association of mortality in models with and without adjustment for previous comorbidities as risk factors. Results: Of 897 patients aged 19-107 years hospitalized with COVID-19, 398 aged ≥ 60 years were included. AKI was observed in 220 patients (55.27%), with stages 1, 2, and 3 in 25.87%, 5.52%, and 23.86%, respectively. Dialysis was required in 73 patients with AKI (33.18%), most of them were at stage 3 (91.89%). Fifty-four patients on dialysis died (73.97%). Increased AKI severity was associated with mortality even after removing the influence of associated risk factors (odds ratios 1.78, 2.35, and 3.51 at stages 1, 2, and 3, respectively). Conclusion: AKI was highly common in patients aged 60 years or older hospitalized with COVID-19, and its severity showed a progressive association with hospital mortality.